UPAYA PEMASARAN PARIWISATA PONOROGO MELALUI CITY BRANDING DALAM MENINGKATKAN KUNJUNGAN WISATAWAN (Studi Kasus pada City Branding Kabupaten Ponorogo dengan Tagline “Ethnic Art of Java - Widiana Puji Astuti; Andriani Kusumawati (Fakultas Ilmu Administrasi Universitas Brawijaya, 2018)
This research is based on the fact that Ponorogo Regency as a area that dominant with its local culture starting to implement city branding strategy since 2015 by use the cultural side especially art as a brand. This research is intended to explain (1) city branding process, (2) city branding hexagon implementation analysis , (3) impacts of city branding, and (4) barriers of city branding.The results of this research is city branding Ponorogo through the process of planning, study related potential of Ponorogo which then produces logo and tagline